Influence of Temperature Couple and Steaming Time on the Viability of Plantain (Musa sapientum L.) Bulb in Kisangani, Democratic Republic of Congo - Molongo Mokondande Médard; Muhammad Ridwan; Litucha Bakokola Joseph; Okungo Lotokola Albert; Songbo Kwedugbu Médard; Monde te-Kazangba Gofroid (Budapest International Research in Exact Sciences (BirEx) Journal, 2023)
The present study has for object to observe the influence of couple temperature and duration of the steaming on the rate of vitality of bulb of plantain in Kisangani in Democratic Republic of Congo. In the methodological framework, this study resorted to the steaming of plantain shoots likely to offer the dry heat as the flaming according to the couple temperature and duration to the steaming in the conditions in vitro at the following temperatures and durations: 50 °C; 80 and 100 °C during 1', 3 and 10'. The subjects were set up in a randomized block design. An agricultural greenhouse was set up in which the 3 blocks were arranged and the treatments were as follows: T01: control 1; T02; control 2; T03: control 3; T11: discharge steamed at 50 °C for 1'; T12: discharge steamed at 50 °C for 3'; T13: discharge steamed at 50 °C for 10'; T21: discharge steamed at 80 °C for 1'; T22: Discharge steamed at 80 °C for 3'; T23: Discharge steamed at 80 °C for 10'; T31: Discharge steamed at 100 °C for 1'; T32: Discharge steamed at 100 °C for 3'; T33: Discharge steamed at 100 °C for 10'. The substrate used was sawdust previously disinfected by boiling water at boiling temperature. He obtained the recovery rates of 90% (for the controls; the subjects steamed at 50 °C; 80 °C and 100 °C during 1'; at 80 °C and 100 °C during 3' and finally at 80 °C and 100 °C during 10') and 100% (for the control subjects; those steamed at 50 °C during 1 and 10'). Thus, the banana bulb subjected to 100 °C for 10' cannot lose its vitality.